QUALITY TEACHERS FOR SUSTAINABLE PHYSICAL EDUCATION AND SPORT - Cotton, Wayne (ASEAN Journal of Sport for Development and Peace, 2023)
This paper will report on the What's the Evidence project scoping review findings, which aim to identify indicators of teacher quality from a holistic perspective. This Australian study deliberately deviates from the commonly used professional standards that often only focus on teaching in order to provide a more comprehensive understanding of teacher quality. To achieve this, a scoping review was conducted as the most comprehensive method of examining contemporary research (2011-2021) for indicators of teacher quality. The PRISMA-ScR structure was utilized for the review process, with a team of 11 researchers engaging in multiple screening processes. The original publication total of 20,854 was reduced to 1,078 publications for indicator analysis and coding. Through content analysis guided by our construct of teacher quality, these indicators were categorized into seven sets containing 51 indicator categories. These findings were then explored by teaching areas, including Physical Education.